Decision-making and decisional conflict among couples seeking treatment for infertility - Anguzu, Ronald; Cusatis, Rachel; Fergestrom, Nicole; Cooper, Alexandra; Sandlow, Jay; Schoyer, Katherine D. (APHA., 2019)
Couples have multiple options for trying to treat infertility, and for many, decisional conflict may arise due to lack of information, uncertainty about options and potential risks, or challenges to personal values. We followed 34 opposite-sex couples who sought a new consult together in a reproductive health clinic (n=78).Participants completed semi-structured interviews and self-administered online surveys, including the DecisionalConflict Scale (DCS), at 6 timepoints over 12 months. The DCS assessed decisional conflict, reported as a totaland 5 subscale scores (informed, values clarity, support, uncertainty and effective decision). A DCS total score of25 is associated with implementing a decision. Paired t-tests identified differences in DCS between women and men within couples. Mixed models predicted changes in DCS over time, adjusting for sociodemographic and fertility-related factors. Average DCS scores were highest before the initial consult. Women’s scores were highest on the uncertainty subscale while men’s were highest on the informed subscale. Within couples, men had significantly higher decisional conflict than women pre-consult (48.9 vs. 40.2, p=0.037) and at 2 months (28.9 vs 22.1, p=0.015), but differences at other time points were not significant. In adjusted models, total DCS scores declined over time, with women, on average, reaching the DCS threshold for implementing a decision at 2 months while for men it was not until 4 months. Decisional conflict is high among couples seeking treatment for infertility. On average, women resolved decisional conflict more quickly than men. Decision support that includes both partners is needed.
Keywords: Infertility; Decision-making and decisional conflict; Couples